Acute hypoxic exercise does not alter post-exercise iron metabolism in moderately trained endurance athletes - Govus, A. D.; Abbiss, C. R.; Garvican-Lewis, L. A.; Swinkels, D. W.; Laarakkers, C. M.; Gore, C. J.; Peeling, P. (European Journal of Applied Physiology, 2014)
Purpose This study measured the influence of acute hypoxic exercise on Interleukin-6 (IL-6), hepcidin, and iron biomarkers in athletes. Methods In a repeated measures design, 13 moderately trained endurance athletes performed 5 × 4 min intervals at 90 % of their peak oxygen consumption velocity (vVO2peak) in both normoxic [NORM, fraction of inspired oxygen (F IO2) = 0.2093, 15.3 ± 1.7 km/h] and simulated hypoxic (HYP, F IO2 = 0.1450, 13.2 ± 1.5 km/h) conditions. Venous blood samples were obtained pre-, post-, and 3 h post-exercise, and analysed for serum hepcidin, IL-6, ferritin, iron, soluble transferrin receptor (sTfR), and transferrin saturation. Results Peak heart rate was significantly lower in HYP compared with NORM (p = 0.01); however, the rating of perceived exertion was similar between trials (p = 0.24). Ferritin (p = 0.02), transferrin (p = 0.03), and IL-6 (p = 0.01) significantly increased immediately post-exercise in both conditions, but returned to baseline 3 h later. Hepcidin levels significantly increased in both conditions 3 h post-exercise (p = 0.05), with no significant differences between trials. A significant treatment effect was observed between trials for sTfR (p = 0.01), but not iron and transferrin saturation. Conclusion Acute exercise in hypoxia did not influence post-exercise IL-6 production, hepcidin activity or iron metabolism compared with exercise at the same relative intensity in normoxia. Hence, acute exercise performed at the same relative intensity in hypoxia poses no further risk to an athlete`s iron status, as compared with exercise in normoxia.